Implementasi Metode Design Thinking dalam Perancangan UI/UX Aplikasi Menabung - Arthalia Wulandari, Ika; Sukmasetya, Pristi; Mujito; Asmanto, Budi (Jurnal Ilmiah Sistem Informasi (JISI), 2025)
Mobile-based savings apps offer convenience in financial planning and management.However, many apps still face challenges regarding user experience (UI/UX) quality, which impacts user adoption and satisfaction. Poor user experience is often caused by interfaces that are not user-centered and a lack of understanding of users' needs. To address this issue, the Design Thinking approach, which focuses on empathy and innovative solutions,has become an increasingly popular methodology in application design. This study examines the application of the Design Thinking method in designing the UI/UX of savings apps, focusing on creating an intuitive and easy-to-use interface. The development process follows five main stages: Empathize, Define, Ideate, Prototype, and Test. The results of applying this method show that the Empathize stage helps developers understand users'saving habits and challenges.In contrast, the prototype stage allows for testing design solutions that better align with user expectations. This study also developed a web-based learning application prototype called "Nyelengi", which aims to assist various groups in managing personal finances. The prototype was evaluated using the System Usability Scale (SUS) to measure the quality of the user experience. The SUS calculation result scored 82,indicating reasonable user satisfaction with the app's interface and functionality. This score suggests that the app design produced through the Design Thinking approach effectively provides a user-friendly, intuitive, and easy-to-use experience. This study indicates that the application of Design Thinking can enhance user satisfaction, promote wider adoption of financial technology, and contribute to the development of more innovative and user-responsive applications